Acute toxicity evaluation and immunomodulatory potential of hydrodynamic cavitation extract of citrus peels - Putri, Dyaningtyas Dewi Pamungkas (Open Science Publishers LLP, 2022)
Citrus peels have been explored vastly due to their high methoxy flavonoid contents that show several biological activities, including immunomodulation, anti-inflammation, and chemoprevention. A water-based extraction method, hydrodynamic cavitation (HC), has recently been adopted to obtain a high methoxy flavonoid extract from Citrus reticulata peels in order to increase its acceptance and utilization. Aiming to verify the safety and immunomodulatory potency of this HC extract of citrus peels (HCE-CP), an acute toxicity test and immunomodulatory assay in rats were carried out. The single oral administration of HCE-CP did not show signs of either toxicity or death up to the 15th day even at the highest dosage, resulting in an lethal dose 50 of more than 5,000 mg/kg body weight (BW). In immunomodulatory evaluation, HCE-CP was given orally daily for 11 weeks, induced with lipopolysaccharide (LPS), and the blood was sampled 5 hours after LPS induction. HCE-CP treatments increased the relative weight of the spleen. The dosage of 2,000 mg/kg BW reduced CD4+ T lymphocytes significantly, but not CD8+. Bioinformatics analysis predicted that hesperidin and hesperetin, two major methoxy flavonoids in HCE-CP, target several proteins that are involved in inflammation in LPS-induced lymphocytes. Taking these data together, HCE-CP is not toxic and shows immunomodulatory potency, especially anti-inflammation.